Neotype designation and redescription of adult male and immature stages of Anopheles (Nyssorhynchus) pictipennis (Philippi) (Diptera: Culicidae) - González, Christian R.; Sallum, Maria Anice Mureb (Zootaxa, 2009)
A neotype is designated for Anopheles (Nyssorhynchus) pictipennis (Philippi) and morphological redescriptions are provided for the adult male, male genitalia, fourth-instar larva and pupa. All specimens, including the neotype were collected in Río Mapocho, Santiago, Chile in 1945 / 1946, and were deposited in the Entomological Collection of Faculdade de Saúde Pública, Universidade de São Paulo (FSP-USP), Brazil. The neotype was previously invalidly designated the allotype of An. pictipennis by Lane and Neghme (1946). Illustrations are provided for diagnostic characteristics of the male genitalia, and larval stage.